1998
DOI: 10.1021/ic980035o
|View full text |Cite
|
Sign up to set email alerts
|

Intense Photosensitized Emission from Stoichiometric Compounds Featuring Mn2+ in Seven- and Eightfold Coordination Environments

Abstract: Synthetic, structural and luminescence studies of stoichiometric crown ether compounds of Mn(2+) in well-defined coordination environments were undertaken in an effort to understand the origin of emitting crystal defects found in cubic F23 [(K18C6)(4)MnBr(4)][TlBr(4)](2) crystals (Fender, N. S.; et al. Inorg. Chem. 1997, 36, 5539). The new compound [Mn(12C4)(2)][MnBr(4)](2)[N(CH(3))(4)](2) (3) features Mn(2+) ions in eight- and fourfold coordination environments of [Mn(12C4)(2)](2+) and MnBr(4)(2)(-) respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Compounds of Mn 2+ and 15-crown-5 were prepared in search of crystals with emissive Mn II ions in environments other than tetrahedral or octahedral geometries (Reid et al, 1998(Reid et al, , 1999. In one of these, [Mn(H 2 O) 2 (15-crown-5)]Br 2 , (I), the cation was found to have crystallographically imposed twofold rotation symmetry, with the axis passing through O1, Mn and the midpoint of the C5-C5A bond.…”
Section: S1 Commentmentioning
confidence: 99%
“…Compounds of Mn 2+ and 15-crown-5 were prepared in search of crystals with emissive Mn II ions in environments other than tetrahedral or octahedral geometries (Reid et al, 1998(Reid et al, , 1999. In one of these, [Mn(H 2 O) 2 (15-crown-5)]Br 2 , (I), the cation was found to have crystallographically imposed twofold rotation symmetry, with the axis passing through O1, Mn and the midpoint of the C5-C5A bond.…”
Section: S1 Commentmentioning
confidence: 99%
“…In fact, many catalytic studies in recent years have found that manganese complexes can exhibit a diversity of catalytic oxidation reactions on organic substrates in organic solvents [20,21]. Numerous complexes of terpyridine and oligopyridines with manganese have been investigated because of their interesting structural, redox, photochemical, catalytic, and water oxidation properties [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The good response of the manganese(ii) 4 T 1 ( 4 G) state to changing ligand field strength and symmetry as well as the high sensitivity of luminescence techniques, such as time resolved luminescence spectroscopy, make the Mn 2+ [ 4 T 1 ( 4 G)? 6 A 1 ] emission attractive as a potential diagnostic tool for coordination characteristics of divalent metal ions.…”
mentioning
confidence: 99%
“…1,2 Besides classical four-and six-coordinate oxide and halide species, 3 Mn 2+ [ 4 T 1 ( 4 G)? 6 A 1 ] emission was recently shown to occur in well defined seven-and eight-coordinate environments 4 thereby expanding the range of Mn 2+ coordination environments accessible by luminescence techniques. Herein we demonstrate the diagnostic efficacy of the Mn 2+ [ 4 T 1 ( 4 G)?…”
mentioning
confidence: 99%
See 1 more Smart Citation